Competition between gelation and crystallisation of a peculiar multicomponent liquid system based on ammonium salts - Kapoor, Iti; Schoen, Eva-Maria; Bachl, Jurgen; Kuehbeck, Dennis; Cativiela, Carlos; Saha, Subhadeep; Banerjee, Rahul; Roelens, Stefano; Juan Marrero-Tellado, Jose; Diaz, David Diaz (Soft Matter, 2012)
An exemplar competition between gelation and crystallisation phenomena was examined with an unusual synergistic multicomponent (organo) gelator solution (MGS), which consists of a well-defined methanolic solution of (1R, 2R)-1,2-diaminocyclohexane L-tartrate containing 2.4 equiv. of concentrated hydrochloric acid. The optimal composition of the MGS was determined through meticulous solubility, gelation and structural studies, which support a transient gelation mechanism based on the kinetic self-assembly of the tartrate salt driven by hydrogen-bonding interactions, involving ammonium nitrogen donors and hydroxyl oxygen acceptors, and electrostatic interactions. The hydrochloric acid is involved in the solubilisation of the salt through an ionic dissociation-exchange process, which ends up with the formation-precipitation of (1R, 2R)-1,2-diaminocyclohexane dihydrochloride. As a consequence, an irreversible destruction of the gel takes place, which indicates the metastable nature of this phase that cannot be accessed from the thermodynamically equilibrated state. Gelation of a variety of oxygenated and nitrogenated solvents with moderate polarity occurred efficiently using extremely low MGS concentrations at low temperatures, and the gel phase was confirmed by dynamic rheological measurements. Several features make the described MGS unique: (1) it is a multicomponent solution where each component and its stoichiometry play a key role in the reproducible formation and stabilization of the gels; (2) it is formed by simple, small, and commercially available chiral building blocks (dissolved in a well-defined solvent system), which are easily amenable for further modifications; (3) the gelation phenomenon takes place efficiently at low temperature upon warming up the isotropic solution, conversely to the typical gel preparation protocol; and (4) the formed organogels are not thermoreversible despite the non-covalent interactions that characterize the 3D-network.

C-C Bond formation catalyzed by natural gelatin and collagen proteins - Kuehbeck, Dennis; Dhar, Basab Bijayi; Schoen, Eva-Maria; Cativiela, Carlos; Gotor-Fernandez, Vicente; Diaz, David Diaz (Beilstein Journal of Organic Chemistry, 2013)
The activity of gelatin and collagen proteins towards C-C bond formation via Henry (nitroaldol) reaction between aldehydes and nitroalkanes is demonstrated for the first time. Among other variables, protein source, physical state and chemical modification influence product yield and kinetics, affording the nitroaldol products in both aqueous and organic media under mild conditions. Significantly, the scale-up of the process between 4-nitrobenzaldehyde and nitromethane is successfully achieved at 1 g scale and in good yield. A comparative kinetic study with other biocatalysts shows an increase of the first-order rate constant in the order chitosan < gelatin < bovine serum albumin (BSA) < collagen. The results of this study indicate that simple edible gelatin can promote C-C bond forming reactions under physiological conditions, which may have important implications from a metabolic perspective.
Keywords: biocatalysis; carbon-carbon bond formation; gelatin; Henry reaction; protein

Investigation of C-C bond formation mediated by bombyx mori silk fibroin materials - Kuehbeck, Dennis; Ghosh, Munmun; Sen Gupta, Sayam; Diaz, David Diaz (ACS Sustainable Chemistry & Engineering, 2014)
The formation of C-C bonds is a prerequisite for all life on earth. Understanding the role of proteins in mediating the formation of these bonds is important for understanding biological mechanisms in evolution, as well as for designing ``green catalysts''. In this work, the ability of silk fibroin (SF) proteins to mediate selective C-C bond formation under mild conditions was comprehensively evaluated and compared between different SF-based materials and other proteins. Aqueous SF solution (ASFS), freeze-dried SF (FDSF), mesoporous SF (MPSF), and SF hydrogel (SFHG) materials were prepared and characterized by a variety of techniques including, among others, FE-SEM, ICP-OES, FT-IR, and TGA. The nitroaldol (Henry) reaction, Knoevenagel condensation, and direct aldol reaction were used as models for this study, in which the recovery and reusability of the protein was also evaluated.
Keywords: Aldol-like reactions; C-C Bond formation; Knoevenagel condensation; Proteins; Silk fibroin